PERAN IMAGE TOKO UNTUK MENUNJANG KEBERHASILAN PENGEMBANGAN PRIVATE LABEL OLEH PERUSAHAAN RITEL - KUSTANTO, FILLY (Universitas Katolik Widya Mandala Surabaya, 2013)
Private label has benefits for retailers and consumers. The key to the development of private label is the ability to create a good image store. Existing conditions led the effort to develop a discussion on the role of store image to support the successful development of private labels by retailers. Store image is owned by the consumer perception of the retail companies. When a retailer has a good store image, then when doing development with private label product sales will get the attention and positive response from consumers in the form of an interest in buying the product. This makes private label acceptable to consumers. Retail companies should be able to create a good image store. Effective communication, the experience of consumers, from the physical stores, services, set prices, product quality, and completeness of product sold needs to be done to establish a good image and store private label success.